2021
DOI: 10.1002/ccr3.5240
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of mature cystic teratoma into undifferentiated carcinoma: A case report

Abstract: Malignant transformation of mature cystic teratoma (MCTO) is a rare entity. Even rarer is the transformation of MCTO into undifferentiated carcinoma. We report a case of an 80‐year‐old woman with undifferentiated carcinoma and squamous cell carcinoma component originating from mature cystic teratoma of the ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“… 1 There are two variants: cystic teratomas which are composed of fully mature elements and are usually benign and solid teratomas which are more likely to be malignant. 9 , 10 Primary retroperitoneal teratomas constitute 1 to 11% of retroperitoneal neoplasms and are most commonly found in neonates and in young adults. 2 They occur in female twice than male.…”
Section: Discussionmentioning
confidence: 99%
“… 1 There are two variants: cystic teratomas which are composed of fully mature elements and are usually benign and solid teratomas which are more likely to be malignant. 9 , 10 Primary retroperitoneal teratomas constitute 1 to 11% of retroperitoneal neoplasms and are most commonly found in neonates and in young adults. 2 They occur in female twice than male.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, several studies reported on different cancer components that coexist within the tumor. [9][10][11] These findings suggest that carcinomas arising from MCT may be a specifically highly heterogeneous tumor. Intratumor heterogeneity was observed in many tumors in cross-sectional carcinoma studies and implicated in tumor evolution, therapeutic resistance, and genomic instability.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, various histologic types of malignant tumors arise from MCT, including adenocarcinoma, carcinoid tumor, thyroid carcinoma, sarcoma, adenosquamous carcinoma, and melanoma 8 . Furthermore, several studies reported on different cancer components that coexist within the tumor 9–11 . These findings suggest that carcinomas arising from MCT may be a specifically highly heterogeneous tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry• Immunohistochemistry diagnosing several patients with suspected squamous cell carcinoma of the prostate (Keio University Hospital)[57], ovarian immature teratomas (University of California, San Francisco Medical Center)[51], and malignant transformation of mature cystic teratoma[58] …”
mentioning
confidence: 99%
“…Cont. Myeloid sarcoma (Armed Forces Medical College)[59], lung carcinoid (Precura Center)[60], and diffuse large B-cell lymphoma (Bach Mai Hospital) were diagnosed by flow cytometry[61] • MRI, MR, and computed tomography were used for the visual examination of patients with undiagnosed basaloid carcinoma of the prostate (Royal Marsden Hospital)[69], malignant transformation of mature cystic teratoma (Nepal Cancer Hospital and Research Center)[58], squamous cell carcinoma of the prostate (Keio University Hospital and Qingdao Municipal Hospital)[52,57] • Genome sequencing analysis diagnosed and detected cancerous sequences in patients with ovarian immature teratomas (University of California, San Francisco Medical Center)[51] and squamous cell carcinoma of the prostate (Qingdao Municipal Hospital)[52] …”
mentioning
confidence: 99%